Cultivating Religious Moderation among Dayah Disciples in Aceh: Insights from the Naqshbandiyya al-Waliyya Order - Setiadi, Fadlan Masykura; Zulfikar, Zulfikar; Erawadi, Erawadi (Nadwa: Jurnal Pendidikan Islam, 2024)
This study investigated the role of the Naqshbandiyya al-Waliyya Ṭarīqa in promoting religious moderation among the students of Dayah Mudi Mesra Samalanga, Aceh. Utilizing a qualitative case study approach, the data were collected through interviews, observations, and document analysis. The research aimed to understand how the teachings and spiritual practices of TNW shape a tolerant and balanced religious environment. The findings indicate that TNW’s practices significantly contribute to transforming the students’ attitudes from exclusive to inclusive and tolerant, characterized by high levels of social solidarity and openness towards others, regardless of their religious or ethnic backgrounds. The leadership of Abu Mudi as TNW’s murshid significantly contributes to instilling values of moderation. This study offers a new perspective on the interaction between Sufi rites and the promotion of religious moderation, a topic rarely discussed in previous literature, enriching the discourse on the role of Islamic spiritual movements in fostering peace and tolerance in pluralistic societies.